Effects of microplastics on the functional traits of aquatic benthic organisms: A global-scale meta-analysis. (15th September 2021) - Berlino, M.; Mangano, M.C.; De Vittor, C.; Sarà, G.
Abstract: Microplastics are widespread in the aquatic environment and thus available for many organisms at different trophic levels. Many scientific papers focus their attention on the study of the effects of microplastics on different species at individual level. Here we performed a global scale meta-analysis focusing our work on the study of the effect of microplastics on the functional traits of aquatic benthic organisms. Overall, microplastics showed a moderate negative effect on the examined functional traits of benthic organisms. Our results show that some crucial functional traits, such as those linked to behaviour and feeding, appear to be unaffected by microplastics. In contrast, traits related to the capacity of organisms to assimilate energy are affected. Moreover, traits with possible effects at population level appear to be negatively affected by microplastics. We discuss how the direct impact of organismal performance may have indirect repercussions at higher levels in the ecological hierarchy and represent a risk for the stability and functioning of the ecosystem. Graphical abstract: Image 1 Highlights: We collated and synthetised scientific evidence of microplastics effects on benthos. The meta-analysis focused on functional traits of benthic species of aquatic realms. Microplastics showed a moderate negative effect on the examined functional traits. Quantitative synthesis represents a robust, salient, integrated scientific baseline. Results can inform scientists, stakeholders addressing the decision-making process. Abstract : Our quantitative synthesis on the effects of microplastics on functional traits of benthic species inhabiting aquatic habitats represents a potential step forward from the existing literature focused on plastics occurrence monitoring only.